The positive impact of Telegram bot usage on supporting students' learning processes and outcomes during on-the-job training - Amalia, Yafi Rahma (Indonesian Journal of Curriculum and Educational Technology Studies, 2024)
This study explores the impact of using Telegram bots on student learning outcomes during the on-the-job training program for XI Software Engineering and Game Development program (PPLG) students in the 2023/2024 even semester, during which students missed direct learning. Using a quantitative correlation approach, data were collected through questionnaires, Telegram bot usage, and learning outcomes. The study involved 71 students from two XI PPLG classes, selected through saturated sampling. Data were analysed using normality, linearity, hypothesis tests, and Pearson product-moment correlation with SPSS 26. The results show a significant relationship between Telegram bot usage and learning outcomes, with a correlation of 0.821 (very strong, sig = 0.000 < 0.05). These findings suggest a potential for developing blended learning models that integrate Telegram bots during the on-the-job training program for students.